Strategi Wakil Kepala Sekolah Bidang Kesiswaan dalam Menanamkan Nilai-nilai Kedisiplinan Siswa MTs DDI Ujung Lero - Hardiani Hardiani (Publikasi Indonesia, 2022)
A discipline is an act of obeying every rule that exists in the school. With discipline makes students more orderly and organized in carrying out their lives. Students also understand that discipline is very important for their future because it can build a strong student personality and be expected to be helpful for all parties. This study aims to find out how the strategy of the vice principal in the field of student affairs is in instilling student discipline values and to find out the supporting and inhibiting factors and their solutions in instilling student discipline values. This research was conducted from April-June 2021 at MTs DDI Ujung Lero, Suppa District, Pinrang Regency. The type of research used was qualitative research using observation, interview, documentation, and technical data analysis techniques. In this study, the informants taken were the Principal, Deputy Principal for Student Affairs, one homeroom teacher, two subject teachers, two parents, and two students. The findings of this study show that the vice principal's strategy for student affairs in instilling disciplinary values for students of MTs DDI Ujung Lero, Suppa District, Pinrang Regency is maximal enough than the supporting factors for the vice principal of student affairs to cooperate with each other in disciplining existing students. The inhibiting factor is that some students often come late to school and don't wear uniforms according to the schedule or days determined by the school. The solution to the inhibiting factor is that the vice-principal for student affairs is more assertive in giving warnings of sanctions/punishments by the existing rules to make students more disciplined.